The Relationship between Religious Orientation and Academic Resilience with the Mediation of Spirituality - Maryam Bakhtiarvand; Hassan Nokarizi; Morteza Bakhtiarvand; Samira Bashiri (Randwick International of Social Science Journal, 2023)
The purpose of this research is to investigate the relationship between religious orientation and academic resilience with the mediation of spirituality in medical students. The subjects included 140 students (70 females and 70 males) from different faculties of Shiraz University of Medical Sciences, who were selected in a multi-stage cluster method. The research tools included Aaronson's spirituality scale, Allport and Ross internal and external religious orientations, and the academic resilience scale. In the analysis of the research findings, Multiple Regression was used in the simultaneous hierarchical method in accordance with the steps of Baron and Kenny (1986). The results showed that internal religious orientation was a positive predictor of spirituality and spirituality was a positive and significant predictor of academic resilience. Also, the spirituality variable was a strong mediator in the relationship between religious orientations and academic resilience. Therefore, people's spirituality and religiosity are significant predictors of academic resilience (p≤0.0001).